Regulation of cellular differentiation in Caulobacter crescentus. - Gober, J W (1995)
In Caulobacter crescentus, asymmetry is generated in the predivisional cell, resulting in the formation of two distinct cell types upon cell division: a motile swarmer cell and a sessile stalked cell. These progeny cell types differ in their relative programs of gene expression and DNA replication. In progeny swarmer cells, DNA replication is silenced for a defined period, but stalked cells reinitiate chromosomal DNA replication immediately following cell division. The establishment of these differential programs of DNA replication may be due to the polar localization of DNA replication proteins, differences in chromosome higher-order structure, or pole-specific transcription. The best-understood aspect of Caulobacter development is biogenesis of the polar flagellum. The genes encoding the flagellum are expressed under cell cycle control predominantly in the predivisional cell type. Transcription of flagellar genes is regulated by a trans-acting hierarchy that responds to both flagellar assembly and cell cycle cues. As the flagellar genes are expressed, their products are targeted to the swarmer pole of the predivisional cell, where assembly occurs. Specific protein targeting and compartmentalized transcription are two mechanisms that contribute to the positioning of flagellar gene products at the swarmer pole of the predivisional cell.